O-032 Current trends in endovascular management of traumatic cerebrovascular injury. (4th July 2012) - Kansagra, A; English, J; Sincic, R; Hetts, S
Abstract : Purpose: The role of catheter angiography in diagnosis and management of traumatic cerebrovascular injury has evolved dramatically due to increased adoption of CT and MR angiography and continued refinement of endovascular techniques. The purpose of this study was to identify the modern spectrum of cerebrovascular injury encountered during catheter angiography in the setting of trauma and to examine current patterns of endovascular treatment. Methods: Records of patients undergoing catheter angiography for traumatic craniocervical arterial injury over a 4-year period at a Level 1 trauma center and a quaternary referral center were retrospectively reviewed. Patients without known trauma mechanism were excluded. The sample comprised 100 separate arterial lesions distributed among 39 males and 13 females (mean age 36 years); all patients had antecedent CT or MRI. Injuries were classified according to mechanism, location, type, acuity, and endovascular treatment. Follow-up-imaging and clinical notes were reviewed to identify delayed complications. Results: Of 100 arterial lesions, 81% were related to blunt force trauma. Distribution of lesions by location was 39% cervical, 42% intracranial, and 19% extracranial. The most common injuries were pseudoaneurysm (37%), fistula (29%), and dissection (19%). In total, 41% of lesions underwent endovascular treatment; endovascular treatment rate was 24/71 (34%) for lesions less than 14 days old and 17/29 (59%) for older injuries. Therapy involved coil embolization for 36 (88%) lesions; stents were used as part of treatment for only 8 (20%) lesions. There were a total of 3 (7.3%) immediate neurovascular complications (infarct, intracranial hemorrhage, iatrogenic dissection) resulting in 1 (2.4%) permanent neurologic deficit. No delayed neurovascular complications occurred over a mean period of follow-up of 4.9 months (range 0–30 months), regardless of whether endovascular therapy was undertaken. Conclusion: Strategies for treatment of traumatic cerebrovascular injury continue to evolve. Our recent experience in a large cohort of patients suggests that a relatively high proportion of traumatic arterial lesions identified during catheter angiography are treated by endovascular means, with a low rate of immediate and delayed neurovascular complications. Competing interests: None.